Design for Six Sigma+LeanToolset - Staudter, Christian (Springer, 2017)
The Toolset is a comprehensive collection of the relevant Design for Six Sigma+Lean tools, which are necessary for successfully implementing innovations. All tools are presented in a clear structure, providing a good overview of the methodology. The chronology of the listed tools corresponds to the procedure in a Design for Six Sigma+Lean development project with the stages Define, Measure, Analyze, Design, and Verify. Due to this unique structure by which tools can be found and applied quickly we created a book that facilitates project work in practical use enormously. Migrating from a tool based approach to a question based approach is a decisive success factor in our opinion enabling firstly, increased efficiency of project work for the Project Leader, his team and the associated Stakeholders, and secondly, significantly increasing the probability of success for the respective innovation projects.